Southeast Asia and the enemy beyond : ASEAN perceptions of external threats - Tilman, Robert O. (Boulder : Westview, 1987)
Published under the auspices of the Institute of Southeast Asian Studies, Singapore.
Keywords: Asia, Southeastern -- Foreign relations